5′-fluoro(di)phosphate-labeled oligonucleotides are versatile molecular probes for studying nucleic acid secondary structure and interactions by 19F NMR. Issue 15 (9th June 2020) - Baranowski, Marek R; Warminski, Marcin; Jemielity, Jacek; Kowalska, Joanna
Abstract: The high sensitivity of 19 F nucleus to changes in the chemical environment has promoted the use of fluorine-labeled molecular probes to study structure and interactions of nucleic acids by 19 F NMR. So far, most efforts have focused on incorporating the fluorine atom into nucleobase and ribose moieties using either monomer building blocks for solid-phase synthesis, or nucleoside triphosphates for enzymatic synthesis. Here, we report a simple and efficient synthesis of 5′-fluoromonophosphorylated and 5′-fluorodiphosphorylated oligodeoxyribonucleotides, which combines solid-phase and in-solution synthesis methods and requires only commercially available nucleoside phosphoramidites, followed by their evaluation as 19 F NMR probes. We confirmed that the fluorine atom at the oligonucleotide 5′ end did not alter the secondary structure of DNA fragments. Moreover, at the same time, it enabled real-time 19 F NMR monitoring of various DNA-related biophysical processes, such as oligonucleotide hybridization (including mismatch identification), G-quadruplex folding/unfolding and its interactions with thrombin, as well as formation of an i -motif structure and its interaction with small-molecule ligands.